Various regulations on the existence of n-th order limit language - Siti Hajar, Mohd Khairuddin; Muhammad Azrin, Ahmad; Noraziah, Adzhar (Penerbit UTM Press, 2022)
In molecular biology, recombinant Deoxyribonucleic acid technology has ignited an increase in the interest of new researches. Moreover, the splicing system has generated enthusiasm in developing computational models collaborating with formal language theory. Formal language theory tends to be a natural structure for formalising and investigating DNA computing models from this viewpoint. The work of several researchers who added control structures to the splicing formalism, thus creating universal computation systems, has provided additional inspiration for the study of splicing systems. A splicing system is a conventional model of a set of dsDNA that undergoes the cutting and pasting process with the presence of restriction enzyme and ligase. Previously, an introduction of the n-th order limit language is presented and discussed. The properties and the characteristics of the n-th order limit language are developed and also explained by using examples and sort into a few cases. However, the regulation of the existence of the n-th order limit language is left unintended. In this paper, the factors that restrict the formation of the n-th order limit language are discussed. Several restrictions applied are the length of the rules are not equal and same rules applies on several crossing sites of the initial strings. In addition, some examples are given to show the restriction of the formation of n-order limit language.